The paradox of flexibility: Exploring the dichotomy of employer-initiated flexible working arrangements and return-to-office directives on knowledge workers’ motivation in the contemporary workplace post-Covid-19 - Meintjes, Anel (University of Pretoria, 2025)
Mini Dissertation (MBA)--University of Pretoria, 2024.